CLIMATE CHANGE AND INDIAN AGRICULTURE: जलवायु परिवर्तन और भारतीय कृषि - Kumath, Usha (International Journal of Research -GRANTHAALAYAH, 2015)
Agriculture is the cornerstone of the Indian economy. The most adverse effect of agriculture and climate change is on weak farmers. The productivity of crops has also been adversely affected due to changes in the amount of rainfall. Climate change is also affecting our national income. In many parts of the country, due to scanty rainfall, crops are dried up or swept away by overflowing, which not only reduced the production of food grains but also increased their prices rapidly. Not only has the productivity of crops been affected by climate change, but its quality has also been negatively affected. The increase in temperature has affected soil moisture and productivity. Climate change caused serious water supply problems and increased frequency of droughts and floods. The rise in global temperature will increase the sea level, affecting the livelihood of the people living in the coastal areas. Increasing water level will engulf the sea farms, the land will become alkaline and will not be cultivable. Keeping in mind the serious and far-reaching effects of climate change, such varieties of seeds will have to be developed which are suited to the new season. Such varieties will have to be developed which are capable of withstanding high temperature and drought and floodplain and can also withstand salinity and alkalinity. Along with climate change, we will also have to change the design of crops and their time of sowing. To save Indian agriculture, we have to use our resources judiciously. Such eco-friendly methods have to be given importance in agriculture so that we can maintain the productivity of our land and save the natural resources. भारतीय अर्थव्यवस्था की आधारशिला कृषि है। कृषि एवं जलवायु परिवर्तन का सबसे ज्यादा प्रतिकूल प्रभाव कमजोर कृषक पर पड़ रहा है। वर्षा की मात्रा में परिवर्तन होने से फसलों की उत्पादकता पर भी प्रतिकूल प्रभाव पड़ा है। जलवायु में होने वाला परिवर्तन हमारी राष्ट्रीय आय को भी प्रभावित कर रहा है। देश के बहुत से भागों में अल्प वर्षा से फसलें सूख जाती है या अति-वृष्टि से बह जाती है जिससे न केवल खाद्यानों का उत्पादन कम हुआ बल्कि उनकी कीमते भी तेजी से बढ़ गई। जलवायु परिवर्तन से फसलों की उत्पादकता ही प्रभावित नहीं हुई बल्कि उसकी गुणवत्ता पर भी नकारात्मक प्रभाव पड़ा है। तापमान के बढ़ने से मिट्टी की नमी व उत्पादकता प्रभावित हुई है। जलवायु परिवर्तन से जल आपूर्ति की गंभीर समस्या उत्पन्न हुई तथा सूखे व बाढ़ की बारम्बरता में वृद्धि हुई। वैश्विक तापमान में वृद्धि से समुद्र का जल स्तर बढ़ेगा जिससे तटीय क्षेत्रों मंे रहने वाले लोगों की आजीविका प्रभावित होगी। जल स्तर बढ़ने से समुद्र खेतों को निगल जाएगा भूमि क्षारीय हो जाएगी व खेती योग्य नहीं रहेगी। जलवायु परिवर्तन के गंभीर व दूरगामी प्रभावों को ध्यान में रखते हुए बीजों की ऐसी किस्मों का विकास करना पड़ेगा जो नये मौसम के अनुकूल हो। ऐसी किस्मों को विकसित करना होगा जो अधिक तापमान तथा सूखे व बाढ़ की विभिषिका को सहन करने में सक्षम हो तथा लवणता व क्षारीयता को भी सहन कर सके। जलवायु परिवर्तन के साथ-साथ हमें फसलों के प्रारूप व उनके बोने के समय मंे भी परिवर्तन करना होगा। भारतीय कृषि को बचाने के लिये हमें अपने संसाधनों का न्यायसंगत इस्तेमाल करना होगा। खेती में ऐसे पर्यावरण मित्र तरीकों को अहमियत देनी होगी जिससे हम अपनी भूमि की उत्पादकता को बरकरार रख सके तथा प्राकृतिक संसाधनों को बचा सके।